PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL PEMBELAJARAN MEANS-ENDS ANALYSIS PADA MATERI ARITMETIKA SOSIAL KELAS VII SMP - Mawaddah Ramadhani Miswar (Departemen Matematika, 2021)
This study aims to develop mathematics teaching materials, namely student worksheet based on Mean-Ends Analysis (MEA) learning model on the material social arithmetics for students grade VII that are valid and practical. This study is the development research using a development research model by Plomp model which consists of three stage namely a preliminary research, a prototyping phase, and an asessment phase. From the analysis validition sheet, shows that student worksheets based on Mean-Ends Analysis (MEA) learning model on the material Social Arithmetics for students grade VII have validity value of 88,89% with very valid category. From the the practical criteria of students respons questionaire result, it shows that this student worksheet have practicality percentage is 96,43% with very practical categories. From the result of the validity and practicality, it was conclude that student worksheet based on Mean-Ends Analysis (MEA) learning model on the material social arithmetics for students grade VII can be stated valid and practical. Keywords – Development Reasearch, Student Worksheet, Mean-Ends Analysis (MEA) Learning Model.